Generalized Anxiety Disorder: Diagnosis and Treatment - Cindy Claudia Soen; Irena Monica Hardjasasmita; Aretha Ever Ulitua (Jurnal Muara Medika dan Psikologi Klinis, 2021)
Generalized Anxiety Disorder or GAD is the most common psychological disorder that is characterized by excessive anxiety and worry (expectations of restlessness) where the symptoms last for six months. The ultimate aims of this research are to explain GAD with its three approaches such as humanistic, psychoanalytic and cognitive based on literature review and research evidence and identify the assessment and treatment for GAD. Treatment for GAD consists of various forms of psychotherapy for instance Cognitive Behavior Therapy (CBT) and Acceptance Based Group Behavioral Therapy (ABBT). We believe that the result of this study can be used as reference to find more about generalized anxiety disorder and come up with specific treatment that is more effective.